The role of the esophageal and intestinal microbiome in gastroesophageal reflux disease: past, present, and future - Guan, Yipan; Cheng, Hongjie; Zhang, Naiwei; Cai, Yanmei; Zhang, Qiaoyan; Jiang, Xianyang; Wang, Ao; Zeng, Haixia; Jia, Boyi (Frontiers in Immunology, 2025)
Gastroesophageal reflux disease (GERD) is one of the common diseases of the digestive system, and its incidence is increasing year by year, in addition to its typical symptoms of acid reflux and heartburn affecting the quality of patients’ survival. The pathogenesis of GERD has not yet been clarified. With the development of detection technology, microbiome have been studied in depth. Normal microbiome are symbiotic with the host and can assist the host to fulfill the roles of digestion and absorption, and promote the development of the host. Dysbiosis of the microbiome forms a new internal environment, under which it may affect the development of GERD from the perspectives of molecular mechanisms: microbial activation of Toll-like receptors, microbial stimulation of cyclooxygenase-2 expression, microbial stimulation of inducible nitrous oxide synthase, and activation of the NLRP3 inflammatory vesicle; immune mechanisms; and impact on the dynamics of the lower gastrointestinal tract. This review will explore the esophageal microbiome and intestinal microbiome characteristics of GERD and the mechanisms by which dysbiotic microbiome induces GERD.